Bilateral advancement O-to-H flap or H-plasty_LN.docx - L. Miccio; G. Mioso (PAGEPress Publications, 2023)
A 68 old man presented with an enlarging lesion of the forehead. Clinical diagnosis of basal cell carcinoma was made, and surgical removal was scheduled.